2007
DOI: 10.1007/s00167-007-0345-5
|View full text |Cite
|
Sign up to set email alerts
|

Lateral unicompartmental knee replacement: fixed or mobile bearing?

Abstract: Between May 2001 and May 2003, 233 consecutive Preservation unicompartmental knee replacements (UKR) were performed. Of these, 30 were lateral UKRs (13%) performed in 12 men and 16 women (2 bilateral cases) with a mean age of 67 years (range 36-93 years). A metal-backed mobile bearing tibial component was used in 13 knees and an all-polyethylene fixed bearing tibial component in 17 knees. The patients were reviewed prospectively at 1 and 2 years. The 2 year results show no difference in range of motion or func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…This is similar to what has been achieved in other series of medial and lateral UKRs. 1,24 There are no comparable series of TKR performed for isolated lateral UKR with reported OKS, but in general the OKS following TKR tends to be substantially less than 40. 25,26 The Domed OUKR was introduced in a response to the high dislocation rate seen with previous designs and the unmodified surgical techniques.…”
Section: Discussionmentioning
confidence: 94%
“…This is similar to what has been achieved in other series of medial and lateral UKRs. 1,24 There are no comparable series of TKR performed for isolated lateral UKR with reported OKS, but in general the OKS following TKR tends to be substantially less than 40. 25,26 The Domed OUKR was introduced in a response to the high dislocation rate seen with previous designs and the unmodified surgical techniques.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have compared fixed bearing and mobile bearing results [15-19]. Emerson [15] reported that survivorship analysis based on component loosening and revision showed no statistically significant difference between fixed-bearing and mobile-bearing implants.…”
Section: Discussionmentioning
confidence: 99%
“…Data from 32 studies were available to compare mobile-bearing vs. fixed-bearing implants; 10 studies (n ¼ 2,268) with mobile-bearing implants [14,18,28,32,33,37,38,41,50,53], 18 studies (n ¼ 1,469) with fixed-bearing [8,26,[42][43][44][45][46][47][48][49]27,30,31,[34][35][36]39,40] and 4 additional studies that reported outcomes for both (n ¼ 1,743 mobile-bearing, n ¼ 790 fixed-bearing) [25,29,46,51]. 18 studies had a moderate risk of bias [8,18,[44][45][46][47][48][49][50]53,26,31,33,34,37,39,42,…”
Section: Fixed-vs Mobile-bearing Componentsmentioning
confidence: 99%
“…Data from 15 studies reported the use of all-PE vs. metal-backed fixedbearing implants; 5 studies (n ¼ 267) with all-PE implants [25,34,36,40,53]; 10 studies (n ¼ 660) with metal-baked implants [8,26,27,29,39,[42][43][44][45][46]. Nine studies had a moderate risk of bias [8,26,34,39,[42][43][44][45][46] and six studies had a serious risk of bias [25,27,29,30,36,40].…”
Section: All-pe Vs Metal-backed Components (Fixed-bearing)mentioning
confidence: 99%